Block copolymer [(l-GluA-5-BE)-b-(l-AspA-4-BE)]-based nanoflower capsules with thermosensitive morphology and pH-responsive drug release for cancer therapy. Issue 40 (24th September 2020) - Amgoth, Chander; Chen, Shuai; Malavath, Tirupathi; Tang, Guping
Abstract : Herein, the synthesis of an amino-acid-based di-block copolymer (di-BCP) in-between an l -glutamic acid-5-benzyl ester and L-aspartic acid-4-benzyl ester [(l -GluA-5-BE)- b -(l -AspA-4-BE)] has been reported. Abstract : Herein, the synthesis of an amino-acid-based di-block copolymer (di-BCP) in-between an l -glutamic acid-5-benzyl ester and l -aspartic acid-4-benzyl ester [(l -GluA-5-BE)- b -(l -AspA-4-BE)] has been reported. However, the synthesis of di-BCP of [(l -GluA-5-BE)- b -(l -AspA-4-BE)] was carried out through the facile modified ring-opening polymerization (ROP) without using any surfactants and harmful chemicals. Interestingly, the synthesized [(l -GluA-5-BE)- b -(l -AspA-4-BE)] has been used to design nanoflower capsules (NFCs) with surface-functionalized nanoflakes and petals. Notably, the simple solvent propanol has been used as a dispersing medium for the di-BCP-based powder to observe morphology of NFCs. Moreover, these amino-acid-based NFCs are biocompatible, biodegradable, and bio-safe for mankind usage. Consequently, di-BCP-based NFCs show changes in morphology with different temperature conditions, i.e., at ∼10 °C, ∼25 °C (RT), and ∼37 °C (body temperature). Furthermore, the average thickness of the surface-functionalized nanopetals has been calculated as ∼324 nm (in diameter). Similarly, the average distance between petals is calculated as 3.6 μm and the pore depth is ∼21 nm. Additionally, the porosity throughout the surface of capsules in-between nanopetals is an advantageous characteristic feature to improve the drug/paclitaxel (PTX) loading capacity. It is a unique and novel approach to design NFCs, which are a potential payload for nanomedicine and cancer therapy. Furthermore, NFCs were used to evaluate the loading efficacy of drugs and showed ∼78% (wt/wt%) of the PTX loading. Moreover, NFCs showed ∼74% drug release at physiological body temperature. Thus, NFCs showed remarkable release at acidic pH medium. However, PTX released from NFCs showed greater cell inhibition ( i.e., ∼79%) with an increase of the PTX concentration after 24 h incubation over HeLa (human epithelial cervical cancer) cells. Besides, PTX released from NFC showed significant (∼34%) cell killing capacity. Such promising NFCs are recommended for breast, liver, and lung cancer therapeutics.